Ultrasonic assisted nanomanipulations with atomic force microscope - Lytvyn, P.M.; Olikh, O.Ya.; Lytvyn, O.S.; Dyachyns’ka, O.M.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Demonstrated experimentally in this work was the possibility of controlled handling the nanoparticles with the size from 50 up to 250 nm on a semiconductor surface by using an atomic force microscope under conditions of acoustic excitation. It has been shown that the selective transport of particles of a certain size is possible owing to the change of an ultrasonic vibration amplitude. Also in this study, possible mechanisms in which ultrasound may influence the particle-surface interaction and the probe-particle (surface) interaction have been analyzed.